Improving irrigation efficiency will be insufficient to meet future water demand in the Nile Basin - Elshamy, M.E. (2020)
We applied SPARE:WATER to calculate irrigation demands on the basis of the well-known FAO56 Crop Irrigation Guidelines. Egypt (67 km3 yr−1) and Sudan (19 km3 yr−1) consume the highest share of the 84 km3 yr−1 total (2011). Assuming today’s poor irrigation infrastructure, the total consumption was predicted to increase to 123 km3 yr−1 (2050), an amount far exceeding the total annual yield of the Nile Basin. Therefore, a key challenge for water resources management in the Nile Basin is balancing the increasing irrigation water demand basin-wide with the available water supply. We found that water savings from improved irrigation technology will not be able to meet the additional needs of planned areas. Under a theoretical scenario of maximum possible efficiency, the deficit would still be 5 km3 yr−1. For more likely efficiency improvement scenarios, the deficit ranged between 23 and 29 km3 yr−1. Our results suggest that that improving irrigation efficiency may substantially contribute to decreasing water stress on the Nile system but would not completely meet the demand.